MicroRNA‐93 targets WASF3 and functions as a metastasis suppressor in breast cancer. Issue 6 (29th May 2020) - Shibuya, Naoki; Kakeji, Yoshihiro; Shimono, Yohei
Abstract: Cancer cells with cancer stem cell (CSC) properties initiate both primary tumor formation and metastases at distant sites. Acquisition of CSC properties is highly associated with epigenetic alterations, including those mediated by microRNAs (miRNAs). We have previously established the breast cancer patient‐derived tumor xenograft (PDX) mouse model in which CSC marker CD44 + cancer cells formed spontaneous microscopic metastases in the liver. In this PDX mouse, we found that the expression levels of 3 miRNAs (miR‐25, miR‐93, and miR‐106b) in the miR‐106b‐25 cluster were much lower in the CD44 + human cancer cells metastasized to the liver than those at the primary site. Constitutive overexpression of miR‐93 suppressed invasive ability and 3D‐organoid formation capacity of breast cancer cells in vitro and significantly suppressed their metastatic ability to the liver in vivo. Wiskott‐Aldrich syndrome protein family member 3 (WASF3), a regulator of both cytoskeleton remodeling and CSC properties, was identified as a functional target of miR‐93: overexpression of miR‐93 reduced the protein level of WASF3 in breast cancer cells and WASF3 rescued the miR‐93‐mediated suppression of breast cancer cell invasion. These findings suggest that miR‐93 functions as a metastasis suppressor by suppressing both invasion ability and CSC properties in breast cancers. Abstract : Multiplex microRNA (miRNA) expression analyses of primary and metastasized cancer cells in breast cancer patient‐derived tumor xenograft mouse revealed the downregulation of the miR‐106b‐25 cluster miRNAs in the CD44 + cancer cells metastasized to the liver. Among them, miR‐93 suppressed invasion and organoid formation ability of breast cancer cells, and WASF3 was identified as a functional target of miR‐93. Finally, we found that overexpression of miR‐93 suppressed the metastasis of breast cancer cells in vivo.